136-2x=25x+19

Simple and best practice solution for 136-2x=25x+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 136-2x=25x+19 equation:


Simplifying
136 + -2x = 25x + 19

Reorder the terms:
136 + -2x = 19 + 25x

Solving
136 + -2x = 19 + 25x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-25x' to each side of the equation.
136 + -2x + -25x = 19 + 25x + -25x

Combine like terms: -2x + -25x = -27x
136 + -27x = 19 + 25x + -25x

Combine like terms: 25x + -25x = 0
136 + -27x = 19 + 0
136 + -27x = 19

Add '-136' to each side of the equation.
136 + -136 + -27x = 19 + -136

Combine like terms: 136 + -136 = 0
0 + -27x = 19 + -136
-27x = 19 + -136

Combine like terms: 19 + -136 = -117
-27x = -117

Divide each side by '-27'.
x = 4.333333333

Simplifying
x = 4.333333333

See similar equations:

| n+10=4 | | 13-8x=65-22x | | -50-10x=8x+22 | | 3x^3(2x^5+10x^4-6)= | | -10n=100 | | 133-4x=6x+13 | | 3x(2x^5+10x^4-6)= | | v+1=0 | | 1x^2-1x=30 | | 1x^2-7x=60 | | 2x+13=61-4 | | n-10=-15 | | -7x^9(4x^3-x^2+x)= | | 4x+27=13x-54 | | v-8=-17 | | (0.2xy)+7=24 | | 4x(5x+20)= | | (.33xy)+10=.66 | | 3k=3 | | (.25xm)-3=5 | | X^2+46=0 | | 1x^2-9x=36 | | n+4=-3 | | (2x+5)(x-3)=6 | | x^2-20x-16=0 | | x^2+4x-396=0 | | 7n=-28 | | x^2-2x=2x-2 | | -9n=-45 | | 4x^2+14x=0 | | t^2+6t+6=0 | | 7p-7=3p+3 |

Equations solver categories